Acalculous acute cholecystitis during the course of an enteroviral infection. Issue 4 (11th April 2019) - Simões, Ana Sofia; Marinhas, Andreia; Coelho, Paulo; Ferreira, Sandra
Abstract : Gallbladder diseases are uncommon in children. Acalculous acute cholecystitis, although rare, is the most frequent form of acute cholecystitis in childhood. In acalculous acute cholecystitis, clinical presentation and laboratory findings are unspecific, making the diagnosis challenging. Abdominal ultrasonography is the first-line exam. Most cases of paediatric acalculous acute cholecystitis have been described in critically ill patients, but can occur in previously healthy children, without underlying diseases or severe conditions. The authors present a clinical report of a child with acalculous acute cholecystitis and enteroviral infection. Diagnosis, treatment, clinical course and prognosis are described. Pathophysiology, aetiology, diagnosis and treatment of acalculous acute cholecystitis are also discussed.